Interaction of magnetic nanoparticles with phospholipid films adsorbed at a liquid/liquid interface - COEY, JOHN; MONZON, LORENA (My University, 2015)
The interaction of Co hexagonal magnetic nanoparticles (MNPs) with distearoyl phosphatidyl glycerol (DSPG) and distearoyl phosphatidic acid (DSPA) films adsorbed at a water/1,2-dichloroethane interface is studied employing cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), capacity curves and interfacial pressure–area isotherms. DSPA and DSPG adsorb at the interface forming homogenous films and producing a blocking effect on the transfer process of tetraethyl ammonium (TEA+), used as a probe cation. In the presence of Co NPs this effect is reversed and the reversible transfer process for TEA+ is reestablished, to a greater or lesser extent depending on the structuration of the film. Co–DSPA hybrid films have a homogeneous structure while Co-DSPG films present different domains. Moreover, the presence of Co on DSPA film modifies the partition coefficient of the organic electrolyte into the hydrocarbon layer.
PUBLISHED
Keywords: Co hexagonal magnetic nanoparticles (MNPs); Co hexagonal magnetic nanoparticles (MNPs)